Fiqih informasi: mengurai penyebaran hoaks dalam kehidupan sosial kontemporer - Wahyuni, Sri Nur (Maliki Interdisciplinary Journal, 2026)
The spread of false information or hoaxes has become an increasingly widespread phenomenon in the digital era, creating serious impacts on the social life of society. From the perspective of Islamic fiqh, the dissemination of hoaxes contradicts the principles of honesty (ṣidq), verification (tabayyun), and the prohibition of spreading lies (al-kadzdhib), and it can damage social order, individual dignity, and the unity of the community. This study aims to analyze the spread of hoaxes based on fiqh perspectives, classify the types of hoaxes, understand their causes, assess their impacts, and evaluate preventive efforts and the responsibilities of Muslims toward this phenomenon. The research method used is qualitative-descriptive, employing literature studies of the Qur’an, hadith, and the works of classical and contemporary fiqh scholars. The findings show that hoaxes are a reprehensible act that causes social and moral harm, both individually and collectively. The spread of hoaxes is influenced by low digital literacy, a lack of understanding of the principle of tabayyun, emotional motivations, as well as political or economic interests. Fiqh emphasizes the responsibility of Muslims to prevent hoaxes through education, moral development, and the application of communication ethics. Thus, the application of fiqh principles can help build a society that is wiser, more responsible, and capable of preserving social well-being in the face of the digital information flow.